(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In terms of geographical dimension, India is among the largest countries needing efficient means of long-distance transport. Although rivalry exists for different transport modes, the railway has its own unique features and offers passengers more services. This study highlights passenger satisfaction with Indian rail services. The research is limited to the South Western Railway division of Hubli. This analysis will help establish additional policies to enhance passenger satisfaction serve as a secondary research results.